2015
DOI: 10.1007/s13730-015-0175-0
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent acute spontaneous tumor lysis syndrome complicated with multiple organ failure in a patient with pre-existing undiagnosed lung cancer

Abstract: Acute kidney injury, a common complication associated with malignancy, occurs in various clinical situations for numerous reasons. Acute tumor lysis syndrome (TLS) is possibly the most significant cause of acute kidney injury in cancer patients, because it is fulminant at onset and associated with severe metabolic derangements. Acute spontaneous tumor lysis syndrome is rare and most of the related malignancies belong to hematologic malignancies but it has seldom been investigated as bulky or advanced metastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Among factors related to high tumor burden, our data suggested that only metastatic disease, especially in the liver or lungs, significantly increases the likelihood of death due to STLS. Previous literature has proposed metastatic disease, especially in the liver, to be associated with an increased risk for TLS development [ 6 , 20 , 30 , 32 , 33 , 36 38 , 44 , 58 , 59 , 93 , 95 , 96 ]. This is thought to occur due to increased tumor burden resulting in high purine pools and mechanical compression by the lesions [ 6 , 32 , 93 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among factors related to high tumor burden, our data suggested that only metastatic disease, especially in the liver or lungs, significantly increases the likelihood of death due to STLS. Previous literature has proposed metastatic disease, especially in the liver, to be associated with an increased risk for TLS development [ 6 , 20 , 30 , 32 , 33 , 36 38 , 44 , 58 , 59 , 93 , 95 , 96 ]. This is thought to occur due to increased tumor burden resulting in high purine pools and mechanical compression by the lesions [ 6 , 32 , 93 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has proposed metastatic disease, especially in the liver, to be associated with an increased risk for TLS development [ 6 , 20 , 30 , 32 , 33 , 36 38 , 44 , 58 , 59 , 93 , 95 , 96 ]. This is thought to occur due to increased tumor burden resulting in high purine pools and mechanical compression by the lesions [ 6 , 32 , 93 , 95 ]. These may lead to hepatic synthetic dysfunction and impaired uric acid metabolism [ 6 , 32 , 93 , 95 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the seriousness and urgency of the TLS, early prevention and early recognition are vital for reducing mortality. Major risk factors for TLS include but are not limited to a large tumour burden, tumours with a high proliferative rate, highly effective antitumour treatment, liver metastases, and baseline renal insufficiency (Amiri, 2015). According to these risk factors, patients can be divided into low-risk, intermediate-risk, and high-risk groups, which is of central importance to enable stratified management.…”
Section: Discussionmentioning
confidence: 99%